Investigating the Role of Border Community Cooperatives in Regional Development A Case Study of Southern Khorasan - M Jomepour; M. A Talebi (تعاون و کشاورزی, 2011)
A major factor of regions development is the internal economic conditions of that region. Cooperative sector, as one of three components of the economical system, aims to enhance these conditions. In border regions, border cooperatives as ambassadors of border community can play a major role in Development and security of the region.12 such border-community cooperatives have been founded in Southern Khorasan province which has more than 430 Km of common border with the country of Afghanistan. In this study, Darmiyan border-community cooperatives were selected as analysis unit in 2010. These cooperatives operate in the two sub-districts of this county, Gazeek and Tabas- e- Masina. There are 12755 members in these cooperatives, including 2699 families. Sample size was determined to be 140 families. A number of managers of these cooperatives were interviewed and were asked to fill out questionnaires. The similar problems of these cooperatives were analyzed in the field by using qualitative and quantitative methods. In conclusion, the research used research hypotheses to utilized strategic planning method and SWOT analysis and provides various scenarios for these cooperatives in the region & among these some of the strategies & objectives were selected and presented as superior. Also pathology of these cooperatives was presented by using strategies derived from SWOT matrix to provide major suggestion for this region.